2022
DOI: 10.1007/s11904-022-00612-2
|View full text |Cite
|
Sign up to set email alerts
|

Developments in Neuroprotection for HIV-Associated Neurocognitive Disorders (HAND)

Abstract: Purpose of Review Reducing the risk of HIV-associated neurocognitive disorders (HAND) is an elusive treatment goal for people living with HIV. Combination antiretroviral therapy (cART) has reduced the prevalence of HIV-associated dementia, but milder, disabling HAND is an unmet challenge. As newer cART regimens that more consistently suppress central nervous system (CNS) HIV replication are developed, the testing of adjunctive neuroprotective therapies must accelerate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 128 publications
0
19
0
Order By: Relevance
“…The mechanisms underlying this risk are not fully understood but may involve shared neuroinflammatory pathways. [10] Neurological opportunistic infections: • Opportunistic infections that affect the central nervous system, such as toxoplasmosis or cryptococcal meningitis, can contribute to cognitive impairment in individuals with HIV. [11] Psychosocial factors: • Psychosocial factors, including stress, depression, and social isolation, can impact cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying this risk are not fully understood but may involve shared neuroinflammatory pathways. [10] Neurological opportunistic infections: • Opportunistic infections that affect the central nervous system, such as toxoplasmosis or cryptococcal meningitis, can contribute to cognitive impairment in individuals with HIV. [11] Psychosocial factors: • Psychosocial factors, including stress, depression, and social isolation, can impact cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence of higher Central Nervous System Penetrance Effectiveness (CPE) score of cART regimens showing protection against HAND but the clinical picture is complicated by neuropsychiatric side effects of these regimens [40]. The recent introduction of integrase strand transfer inhibitors (INSTI) such as dolutegravir was initially promising due to effectiveness in blocking viral replication but current trial evidence including a 96 week placebo controlled doubleblind intensification study does not suggest any significant effect on HAND [40]. One South African study (2023) suggested reduction in cognitive impairment on commencing dolutegravir but was undertaken in treatment na€ ıve patients commencing cART without a control arm [41].…”
Section: Interventional Approachesmentioning
confidence: 99%
“…There have been recent randomized controlled trials of lithium, and B vitamins as adjuvant treatments in cART-treated PWHA, both of which were unsuccessful [39]. There is some evidence of higher Central Nervous System Penetrance Effectiveness (CPE) score of cART regimens showing protection against HAND but the clinical picture is complicated by neuropsychiatric side effects of these regimens [40]. The recent introduction of integrase strand transfer inhibitors (INSTI) such as dolutegravir was initially promising due to effectiveness in blocking viral replication but current trial evidence including a 96 week placebo controlled double-blind intensification study does not suggest any significant effect on HAND [40].…”
Section: Interventional Approachesmentioning
confidence: 99%
“…Within days of infection, HIV-infected blood monocytes breach the blood-brain barrier (BBB), activating perivascular macrophages and microglia, the principal productively infected cells in the CNS [1,12,13]. The establishment of a latent viral reservoir within microglia underlies the persistent neuroinflammation and immune activation characteristic of HAND, which is lessened but not abolished by cART [1,14].…”
Section: Introductionmentioning
confidence: 99%